The effect of tender offer in experimental asset market - Chen, Yufei (2016)
Tender offer is one of the most commonly used measures for corporate takeover. Empirical research suggest a significant impact of tender offer announcement on asset market, namely stock pricing and trading liquidity. In this paper, we design and conduct an experiment under the framework suggested by Smith, Suchanek and Williams (1988) to investigate this impact. Our experiment results suggest that tender offer intensifies price bubbles, and that takeover competition significantly increases market liquidity.